2010
DOI: 10.1007/s10637-010-9442-2
|View full text |Cite
|
Sign up to set email alerts
|

Activity of topotecan given intravenously for 5 days every three weeks in patients with advanced non-small cell lung cancer pretreated with platinum and taxanes: a phase II study

Abstract: Topotecan, a semi-synthetic camptothecin analogue with topoisomerase I interaction, has shown to be an active agent in the treatment of advanced refractory lung cancer. This paper describes the authors' experience with this drug when used as a single agent in patients (pts) with advanced non-small cell lung cancer (NSCLC) refractory to platinum- and taxane-containing chemotherapy regimens. Thirty-five patients with NSCLC refractory to previous chemotherapy and KI ≥ 60% were included in the study. Their charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…TPT is FDA approved as a second-line drug for the treatment of advanced ovarian, cervical, and small cell lung cancers ( McGuire et al, 2000 ; Monk et al, 2009 ; O'Brien et al, 2007 ). The limited number of clinical trials using TPT as a single agent for NSCLC have demonstrated response rates (RR) and median OS ranging from 0 – 25% and 40 – 74 weeks as first-line and 2.8 – 8% and 10 – 34 weeks in second-line settings, respectively ( Gonzalez et al, 2010 ; Jones et al, 2008 ). Two recent phase II and phase III clinical trials, demonstrated that oral TPT in unselected NSCLC patients is as effective as docetaxel, the FDA approved second-line drug for NSCLC ( Gonzalez et al, 2010 ; Jones et al, 2008 ; Ramlau et al, 2006 ; Weitz et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TPT is FDA approved as a second-line drug for the treatment of advanced ovarian, cervical, and small cell lung cancers ( McGuire et al, 2000 ; Monk et al, 2009 ; O'Brien et al, 2007 ). The limited number of clinical trials using TPT as a single agent for NSCLC have demonstrated response rates (RR) and median OS ranging from 0 – 25% and 40 – 74 weeks as first-line and 2.8 – 8% and 10 – 34 weeks in second-line settings, respectively ( Gonzalez et al, 2010 ; Jones et al, 2008 ). Two recent phase II and phase III clinical trials, demonstrated that oral TPT in unselected NSCLC patients is as effective as docetaxel, the FDA approved second-line drug for NSCLC ( Gonzalez et al, 2010 ; Jones et al, 2008 ; Ramlau et al, 2006 ; Weitz et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…The limited number of clinical trials using TPT as a single agent for NSCLC have demonstrated response rates (RR) and median OS ranging from 0 – 25% and 40 – 74 weeks as first-line and 2.8 – 8% and 10 – 34 weeks in second-line settings, respectively ( Gonzalez et al, 2010 ; Jones et al, 2008 ). Two recent phase II and phase III clinical trials, demonstrated that oral TPT in unselected NSCLC patients is as effective as docetaxel, the FDA approved second-line drug for NSCLC ( Gonzalez et al, 2010 ; Jones et al, 2008 ; Ramlau et al, 2006 ; Weitz et al, 2000 ). Large intra-study differences in OS ranging from 4 – 59 and 2 – 46 weeks were also seen when TPT was used as a first- or second-line therapy for NSCLC patients, respectively ( Gonzalez et al, 2010 ; White et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gonzalez et al [ 20 ] conducted a phase II study to determine the activity of TPT given at a dose of 1.25 mg/m 2 IV for 5 days every 3 weeks in patients with advanced NSCLC pretreated with platinum and taxanes. This study showed that IV TPT at this dose and administration schedule displayed scant activity in terms of response rate in individuals with advanced NSCLC previously treated with platinum and taxanes.…”
Section: Phase II Clinical Trials Of Tpt As Single-agent Therapymentioning
confidence: 99%
“…Followed the promising results obtained from phase I trial with topotecan [35], a dose of 1.5 mg/m 2 /day was selected for phase II/III evaluation. This regimen has been shown to have activity in recurrent ovarian cancer [36], relapsed small cell lung cancer [37], non-small cell lung cancer [38,39], and breast cancer [40]. Topotecan has been found effective in combinatorial treatment with pegylated liposomal doxorubicin in brain tumor [41], platinum resistant ovarian and peritoneal cancer [42,43].…”
Section: Topotecanmentioning
confidence: 99%